A Case Report on Zinner Syndrome – A Rare Congenital Malformation - Sunkara, Haripriya; Kumar, Adusumilli Pramod; Rao, Giduturi Srinivasa; Gottumukkala, Avinash (Indian Journal of Pharmacy Practice)
Zinner syndrome is a rare congenital triad of unilateral seminal vesicle cyst, unilateral ejaculatory duct obstruction or agenesis and ipsilateral renal agenesis. Here we present a case of a healthy 22 year-old male presenting with complaints of low back ache and painful ejaculation since 6 years. On radiological evaluation with MRI abdomen and pelvis, a horse shoe kidney with atrophy of right limb and a right seminal vesicle cyst was revealed. Because of persistence of symptoms after a trail of medical management, the patient opted for surgical intervention. Laparoscopic seminal vesicle cyst excision was done and vas deference was dismembered from communication with ureter. Post operatively, patient’s symptoms were dramatically improved.
Keywords: Zinner syndrome; Duct obstruction; Renal agenesis; Laparoscopy; Cyst excision.